Penerapan Total Productive Maintenance (TPM) Pada Perawatan Mesin Cutter di PT. XYZ - Ganep Muhaemin; Asep Erik Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
The development of the global industry in using technology is forcing increasingly fierce competition. This is supported by technological developments with reliable and quality machines. The result is an impact on the ability to create products of sufficient quality and quantity. To compete with other companies, the machine's willingness to carry out production plays an important role. The decline in the function of the machine results in reduced production yields and also the quality of production. Machine maintenance is one way that is intended to maintain the stability of production in a company. The term maintenance is widely known, but has grown to be known as Total Productive Maintenance (TPM). PT. XYZ produces printing and non-printing paper bags. In the NCR department, the cutter machine area is still experiencing 25% more machine problems than other areas so that further analysis is needed from the TPM index assessment through the OEE score. Therefore, the purpose of this study is to determine the value of OEE as an analysis of the six big losses and recommendations for improvement. The research methodology is direct observation and interviews with stakeholders related to the cutter machine area. The result is that the OEE values ​​in October, November, and December are less than the JPIM standard. In this regard, the company can conduct training for production operators on machine maintenance procedures. Meanwhile, the maintenance department is responsible for the maintenance of the machine